Effects of hydrogen sulfide on high glucose-induced glomerular podocyte injury in mice - Liu, Ye (Int J Clin Exp Pathol, 2015)
The aim of this study was to assess the effects of hydrogen sulfide on high glucose-induced mouse podocyte (MPC) injury and the underlying mechanisms. Mouse podocytes were randomly divided into 4 groups, including high glucose (HG), normal glucose (NG), normal glucose + DL-propargylglycine (PPG), and high glucose + NaHS (HG + NaHS) groups for treatment. Then, ZO-2, nephrin, β-catenin, and cystathionine γ-lyase (CSE) protein expression levels were determined by western blot. We found that high glucose significantly reduced nephrin, ZO-2, and CSE expression levels (P<0.05), and overtly elevated β-catenin amounts (P<0.05), in a time-dependent manner. Likewise, PPG at different concentrations in normal glucose resulted in significantly lower CSE, ZO-2, and nephrin levels (P<0.05), and increased β-catenin amounts (P<0.05). Interestingly, significantly increased ZO-2 and nephrin levels, and overtly reduced β-catenin amounts were observed in the HG + NaHS group compared with HG treated cells (P<0.01). Compared with NG treated cells, decreased ZO-2 and nephrin levels and higher β-catenin amounts were obtained in the HG + NaHS group. In conclusion,CSE downregulation contributes to hyperglycemia induced podocyte injury, which is alleviated by exogenous H(2)S possibly through ZO-2 upregulation and the subsequent suppression of Wnt/β-catenin pathway.